2019
DOI: 10.3390/catal9020157
|View full text |Cite
|
Sign up to set email alerts
|

Electropositive Promotion by Alkalis or Alkaline Earths of Pt-Group Metals in Emissions Control Catalysis: A Status Report

Abstract: Recent studies have shown that the catalytic performance (activity and/or selectivity) of Pt-group metal (PGM) catalysts for the CO and hydrocarbons oxidation as well as for the (CO, HCs or H2)-SCR of NOx or N2O can be remarkably affected through surface-induced promotion by successful application of electropositive promoters, such as alkalis or alkaline earths. Two promotion methodologies were implemented for these studies: the Electrochemical Promotion of Catalysis (EPOC) and the Conventional Catalysts Promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 122 publications
(424 reference statements)
2
26
0
Order By: Relevance
“…Interestingly, it was found that alkali addition had a greater impact on the catalyst with the low Ru loading (0.5 wt.%), in comparizon to that with the high Ru loading (5 wt.%), and an optimal Na loading of 0.2 wt.% was obtained for the former (i.e., 0.5 wt.% Ru/0.2 wt.% Na-TiO 2 ). These results agree with the general features of alkali promotion on several catalytic systems, which typically obey a volcano-type behavior with respect to the promoter/metal ratio; low promoter/metal ratios are inefficient to induce succesful promotion, high promoter/metal ratios lead to over-promotion (poisoning) [32]. The catalytic activity and CH 4 selectivity were promoted according to the following order with respect to the alkali identity: TiO 2 (unpromoted) < Li ≈ K < Cs < Na, as shown in Figure 1 [33].…”
Section: Screenings Of Various Alkalimetalssupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, it was found that alkali addition had a greater impact on the catalyst with the low Ru loading (0.5 wt.%), in comparizon to that with the high Ru loading (5 wt.%), and an optimal Na loading of 0.2 wt.% was obtained for the former (i.e., 0.5 wt.% Ru/0.2 wt.% Na-TiO 2 ). These results agree with the general features of alkali promotion on several catalytic systems, which typically obey a volcano-type behavior with respect to the promoter/metal ratio; low promoter/metal ratios are inefficient to induce succesful promotion, high promoter/metal ratios lead to over-promotion (poisoning) [32]. The catalytic activity and CH 4 selectivity were promoted according to the following order with respect to the alkali identity: TiO 2 (unpromoted) < Li ≈ K < Cs < Na, as shown in Figure 1 [33].…”
Section: Screenings Of Various Alkalimetalssupporting
confidence: 85%
“…Alkali and especially alkaline earth metal promotion of the CO 2 methanation reaction has been a quite popular route in recent years. These types of metals are cheap, abundant and can potentially promote the CO 2 methanation reaction by increasing support basicity and by introducing oxygen vacancies, thus favouring the initial CO 2 chemisorption [28,30,31], or even by strongly modifying the work function and thus the chemisoptive properties of the metal active phase [32]. Hereby, we categorize the different alkali and alkaline earth metal promoters starting from alkalimetals.…”
Section: Alkali and Alkaline Earth Metals As Promoters Of The Co 2 Mementioning
confidence: 99%
“…The rates increase due to EPOC and supporting the catalysts on active metal oxides were similar in the case of platinum and ruthenium catalysts 11 . Furthermore, many highly dispersed electrochemically promoted systems have been established, rendering the practical application of EPOC more attractive 11,12,[21][22][23][24][13][14][15][16][17][18][19][20] . Experimentally, the origin of EPOC is mostly explained by the electrochemically induced promoters (see Figure 1), which have been substantiated by many in-situ and ex-situ techniques: x-ray photoelectron spectroscopy (XPS) 25,26 , in-situ XPS 27 , temperatureprogrammed desorption (TPD) 28,29 , scanning tunneling microscopy (STM), photoemission spectroscopy (PES) 30 , in-situ AC impedance spectroscopy 31,32 , and isotopic exchange 33 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, three comprehensive review articles covering several major topics and directions in emissions control catalysis subject were published in this special issue. The review of the guest editors (Yentekakis I., and Vernoux P.) and co-workers [17] concerns mainly the of CO, CHs, and NO x emissions abatement from stoichiometric, lean burn, and diesel engines exhausts, addressing the literature that concerns the electropositive promotion by alkalis or alkaline earths of platinum group metals (PGMs) that have found to be extremely effective for the related three-way and lean-burn reactions and catalytic chemistry. The review of Smirniotis P. and co-workers [18] concerns the selective catalytic reduction of NO x with NH 3 (NH 3 -SCR of NO x ) focusing to low temperature applications that is a highly desirable perspective, and finally the review of Bogaerts A. and co-workers [19] covering a hot recent trend in emissions control implicating cyclic economy strategies, that is the conversion and utilization of CO 2 for the production of value-added chemicals.…”
Section: Special Issue Contributions and Highlightsmentioning
confidence: 99%
“…Alkali metals as surface-promoters of platinum group metals (PGMs) have shown remarkable promotional effects on the vast majority of reactions related to the emissions control catalysis either they are applied by traditional routes (e.g., impregnation) or electrochemically, via the so called, concept of the electrochemical promotion of catalysis (EPOC) or non-faradaic electrochemical modification of catalytic activity (NEMCA effect) [14,15]. In the comprehensive review of Yentekakis et al [17] published in this Special Issue, more than 120 papers on the subject were collected and discussed comparatively after classification in groups, on the basis of the specific reaction promoted, e.g., (CO, HCs, or H 2 )-SCR of NO x , and CO or hydrocarbons oxidation. The authors also present and analyze, by means of indirect (kinetics) and direct (spectroscopic) evidences, a mechanistic model for the mode of action of electropositive promoters, which consistently interprets all the observed promoting phenomena.…”
Section: Review Contributionsmentioning
confidence: 99%